Sermaye Akımlarının Temel Makroekonomik Göstergeler Üzerindeki Etkileri: Türkiye Örneği-1989:III-1999:IV - Aysu Insel; Nesrin Sungur (Turkish Economic Association, 2003)
– The purpose of this paper is to analyze the effects of foreign capital flows on the selected macroeconomic indicators in Turkey, for the period 1989-1999. This paper investigates empirically the relationships between the foreign capital flows and the selected macroeconomic indicators. It is concluded that the capital flows in Turkey increase the volatility of the real and financial indicators and thus play an important role to contribute the economic instability.
Keywords: 330